Impact of the COVID-19 pandemic on orthopedic surgeon in Pakistan - Muzzammil, Muhammad; Jahanzeb, Syed; Asghar, Ali; Jabbar, Saadia; Waheed, Hira (International Journal of Research in Orthopaedics, 2020)
Background: The objective of our study is to assess the impact of COVID-19 pandemic on clinical practice as well as psychological impact on orthopedic surgeons of Pakistan. Method: An online survey involving orthopedic surgeons through social media platforms like WhatsApp and Facebook and also through email, to assess the impact of COVID-19 pandemic. Our survey also aims to evaluate their state of mind and physical as well as emotional wellbeing in the wake of COVID-19 pandemic. Results: Among 77 respondents, mostly 31 (40.3%) were consultant and mostly 28 (36.4%) having experience in field of orthopedics was between 5-10 years. This data revealed 48 (62.3%) respondents did not received any specific training or recommendations about COVID pandemic from their institute and only 37 (48.1%) reported they are well informed on latest COVID guidelines. Interestingly, this data revealed the willingness of orthopedic surgeons 30 (39%) to take care of COVID-19 positive patients in ICU. 67 (87%) feel anxious, stressed, furious, angry or depressed due to pandemic and most common fear among them was to infect their family members followed by getting infected and loss of their life and health. 40 (51.9%) did not think their institute is well equipped to deal COVID pandemic. Conclusions: Orthopedic community nevertheless have to play an important role in the face of an increasing psychological and emotional stress which comes from working in a post COVID era. The dread of getting infected while treating and the sinking feeling of spreading the contagion to their loved ones has put a massive toll on the emotional well-being and needs to be addressed through open and fair discussion.